1991
DOI: 10.1523/jneurosci.11-07-02102.1991
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal hyperthyroidism alters hippocampal circuitry and improves radial-maze learning in adult mice

Abstract: Inbred mice show strain-specific differences in the hippocampal mossy fiber projection. These differences are most pronounced in the portion of the projection that forms synaptic connections with the basal dendrites of the CA3 pyramidal neurons [intra- and infrapyramidal mossy fiber (IIP-MF) projection]. We have previously demonstrated that the extent of the IIP-MF subfield is positively correlated with the capacity to perform a spatial radial-maze task and that an experimentally induced enlargement of the II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…In addition to these inherent genetic differences in IPB length, changes in IPB length have been induced in animals with over-exposure to certain hormones or endocrine tissues. It was observed that hyperthyroidism in mice induced by daily injections of thyroxine from postnatal day 0 (P0) to P11 resulted in an increased IPB area [Schwegler et al, 1991]. Further, the hyperthyroid animals in this study had fewer errors in a radial maze task than controls, which is in agreement with the performance of mice with a long IPB mentioned above.…”
Section: Introductionsupporting
confidence: 89%
“…In addition to these inherent genetic differences in IPB length, changes in IPB length have been induced in animals with over-exposure to certain hormones or endocrine tissues. It was observed that hyperthyroidism in mice induced by daily injections of thyroxine from postnatal day 0 (P0) to P11 resulted in an increased IPB area [Schwegler et al, 1991]. Further, the hyperthyroid animals in this study had fewer errors in a radial maze task than controls, which is in agreement with the performance of mice with a long IPB mentioned above.…”
Section: Introductionsupporting
confidence: 89%
“…Transient neonatal hyperthyroidism produces an altered hippocampal morphology with larger mossy fiber terminal fields in the hippocampal CA3 region (Lauder and Mugnaini, 1977; Lipp et al, 1988). These morphological changes are accompanied by an improvement of spatial memory in the radial maze, but there is also an impairment of two‐way active avoidance learning in the shuttle box (Lipp et al, 1988; Crusio and Schwegler, 1991; Schwegler et al, 1991). Thus, thyroid hormones influence both cognitive (spatial learning, two‐way avoidance learning), and emotional factors (two‐way avoidance learning).…”
Section: Hyperthyroidism and Brain Development Interactionsmentioning
confidence: 99%
“…After each test session, the mice are evaluated for three parameters: working memory errors, reference memory errors, and total arm entries. Working memory errors are classified as reentries into baited arms that had been previously entered during the test session, and reference memory errors are classified as entry into non-baited arms [104, 105]. The mice were considered to have learned the task when the number of working memory errors reached zero and the number of reference memory errors is one [103, 105].…”
Section: Cognitive Deficits In Pdmentioning
confidence: 99%